Lecturers’ Perceptions and Practices of Humor in EFL Classrooms - Siti Fadhilah; Johannes Ananto Prayogo; Francisca Maria Ivone (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: This study aims to explore lecturers’ perceptions and practices of humor usage in EFL classrooms. This qualitative study used questionnaires and interview protocols to get data from two senior English lecturers who use humor in their classrooms at an English department of a public university in Indonesia. The result reveals that humor, particularly jokes and spontaneous humor are practical and beneficial for learning English in higher education. However, in delivering humor, the lecturers should consider the setting (time and place), college students’ vocabulary level, age, and sex; humor should not offend them culturally and be understandable.